2014
DOI: 10.1089/rej.2014.1561
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Birds to Serve as Pathology-Free Models of Type 2 Diabetes, Part 2: Do High Levels of Carbonyl-Scavenging Amino Acids (e.g., Taurine) and Low Concentrations of Methylglyoxal Limit the Production of Advanced Glycation End-Products?

Abstract: In our previous publication, we reported on the advantages of using birds as a pathology-free model of type 2 diabetes mellitus (T2DM). Using this new perspective, we observed that birds are missing the RAGE gene, considered an important factor in the development of diabetic complications. In this article, we identify two additional Maillard reaction-related characteristics of birds that have the potential to account, in part, for avian ability to cope successfully with chronic hyperglycemia. First, compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 117 publications
1
9
0
Order By: Relevance
“…From these results, we selected 500 µM concentration of MGO for further mechanism study. Similarly, Szwergold et al demonstrated a range of concentration (340-920 µM) of carbonyl-scavenging amino acids and low concentration of MGO in blood plasma of birds [31]. This study gave us an idea for the treatment concentration of l-Cysteine as we hypothesized that l-cysteine might interact with MGO to lower MGO-induced toxicity.…”
Section: Resultssupporting
confidence: 57%
“…From these results, we selected 500 µM concentration of MGO for further mechanism study. Similarly, Szwergold et al demonstrated a range of concentration (340-920 µM) of carbonyl-scavenging amino acids and low concentration of MGO in blood plasma of birds [31]. This study gave us an idea for the treatment concentration of l-Cysteine as we hypothesized that l-cysteine might interact with MGO to lower MGO-induced toxicity.…”
Section: Resultssupporting
confidence: 57%
“…An evolutionarily unconserved trait in avian muscle metabolism is unparalleled by an insistent energy system that is always in the “ on-state ” required for adaptive flight maneuvers. Notably, GLDH critically regulates amino acid metabolism and is present in high concentrations within liver, heart, muscle, and kidney mitochondria where it catalyzes the (i.e., reversible) oxidative deamination of l -glutamate to α -ketoglutarate [1, 7, 8, 11, 13], thereby providing energy via the citric acid cycle-dependent ATP. The GLDH activity is particularly important within pancreatic β - cells, which secretes insulin in an ATP:ADP ratio-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…TAU is rich in the blood of layer-type chickens ( Takawaki et al., 2013 ) and in the liver and thigh muscle of broilers ( Huang et al., 2014 ). TAU level in blood is 6- to 11-fold higher in avian species than in humans ( Szwergold and Miller, 2014 ). Moreover, TAU is an essential nutrient against oxidative damage in mammal ( Brosnan and Brosnan, 2006 ) and in broilers ( Xu et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%